Analysis of Soil Bacterial Diversity from Tropical Rainforest and Oil Palm Plantation In Jambi, Indonesia by 16S rRNA-DGGE Profiles - Risky Hadi wibowo; Nisa Rachmania Mubarik; Iman Rusmana; Maggy Thenawidjaya Suhartono; Sipriyadi Sipriyadi; Masrukhin Masrukhin (Journal of Tropical Biodiversity and Biotechnology, 2022)
Oil palm plantations are the most invasive land use changes in Southeast Asia. It must have affected unique natural biodiversity. This study aimed to investigate the diversity of soil bacteria based on 16S rRNA gene profiles from tropical forest and oil palm plantation in Jambi Province, Indonesia. Soil sample was taken from tropical forest and oil palm plantation from Jambi province, Indonesia. The forest site is in Bukit Duabelas National Park, and the nearby oil palm plantation is in Sarolangun District, Jambi Province, Indonesia. The diversity of bacterial communities from topsoil was studied using Denaturing gradient gel electrophoresis (DGGE) of 16S rRNA gene and common biodiversity indices. PCR amplification of 16S rRNA gene was successfully conducted primers-using 33F/ 518R primers. Phylogenetic approach was used for revealing the community shift of bacterial phyla and genera in both areas. Phylogenetic analysis showed there were 4 phyla of bacteria i.e., Firmicutes, Alphaproteobacteria, Gammaproteobacteria, and Actinobacteria, respectively. Actinobacteria was the most dominant group in both areas. The composition of soil bacterial community in the oil palm plantation, based on total number of bands 16S rRNA generated from DGGE was richer than that in the Bukit Dua Belas National Park. It was probably caused by plantation year circle more than 10 years and routine activities during the plantation management, such as applications of agricultural lime, herbicide and fertilizer.